Found voices a research-based screenplay on the Nicole-Subic rape case and rape myths - Carlos, Christine H. 1962- (College of Mass Communication, University of the Philippines Diliman, 2013)
"Found Voices: A Resaerch-Based Screenplay On The Nicole-Subic Rape Case and Rape Myths" has the elements of interracial relationships, gender politics and postcolonial issues which have always interested the researcher who studied and analyzed the case of Nicole from a feminist perspective. Feminist lawyers and writers who analyzed rape in recent years have seen the role of rape myths in creating suspicion on the validity and genuineness of rape cases. They have also observed the phenomena of blaming the victim. Although several types of rape exist, stranger rape is often used as the benchmark to judge if a rape is genuine or just a false accusation. The social research on rape aided the researcher who is also a filmmaker in understanding the Nicole-subic rape case. Furthermore, the researcher analyzed the decision of the Court of Appeals, the Philippine-American relationship, the US military in the Philippines and the US-Philippine Visiting Forces Agreement (VFA) in relation to the Nicole-Subic rape case. The researcher combined social sciences resaerch methods with the narratives found in the Nicole-Subic rape case and other narratives of interviewees from Subic and Zamboanga and incorporated these elements in creating a full-length screenplay. The story of the protagonists in the screenplay Stella portrays in literal rape while the other characters; the milieu of Subic and the outcome of the case depict the rape of Philippine sovereignty. The script or screenplay utilized basic scriptwriting principles and the Found Story Paradigm of Armando "Bing" Lao."